Effects of Oxidized Metal Powders on Pore Defects in Powder-Fed Direct Energy Deposition - Jong-Youn Son; Ki-Yong Lee; Seung Hwan Lee; Chang-Hwan Choi (Micromachines, 2024)
Laser-based additive manufacturing processes, particularly direct energy deposition (DED), have gained prominence for fabricating complex, functionally graded, or customized parts. DED employs a high-powered heat source to melt metallic powder or wire, enabling precise control of grain structures and the production of high-strength objects. However, common defects, such as a lack of fusion and pores between layers or beads, can compromise the mechanical properties of the printed components. This study focuses on investigating the recurrent causes of pore defects in the powder-fed DED process, with a specific emphasis on the influence of oxidized metal powders. This research explores the impact of intentionally oxidizing metal powders of hot work tool steel H13 by exposing them to regulated humidity and temperature conditions. Scanning electron microscopy images and energy-dispersive X-ray spectroscopy results demonstrate the clumping of powders and the deposition of iron oxides in the oxidized powders at elevated temperatures (70 °C for 72 h). Multi-layered depositions of the oxidized H13 powders on STD61 substrate do not show significant differences in cross sections among specimens, suggesting that oxidation does not visibly form large pores. However, fine pores, detected through CT scanning, are observed in depositions of oxidized powders at higher temperatures. These fine pores, typically less than 250 µm in diameter, are irregularly distributed throughout the deposition, indicating a potential degradation in mechanical properties. The findings highlight the need for careful consideration of oxidation effects in optimizing process parameters for enhanced additive manufacturing quality.